Manifestations of Grabar Terms in Grigor Narekatsi’s “Book of Lamentations” - Abajyan, Anna; Yuzbashyan , Anahit (Bulletin of Yerevan University B: Philology, 2024)
The independent and translated literature vocabulary of Old Armenian has been subjected to semantic-etymological and stylistic in-depth study, however, the most significant component of the vocabulary, its term system, still needs further investigation. The semantic-etymological and structural features of Grabar terms, as evidenced by our conducted analysis, demonstrate the necessity for a comprehensive inclusion of their examination within the system. The most prominent feature of Grabar's term system is that it is multi-layered. Each sub-layer has its own characteristic features from stylistic and functional points of view when the content of the given book and the author's art are also important in the aspect of including the semantic nuances of the vocabulary and creating certain stylistic values through them. The given study presents the semantic and stylistic characteristics of Grabar terms in Grigor Narekatsi's poem "Book of Lamentations". The author has used terms representing different semantic layers and sub-layers, for example, e.g. names of animals, household items, terms denoting metals, those meaning the spiritual and physical structure of the body, as well as the ones with religious, legal, and military content. However, the predominance is given to the terms honoring God, which are mostly occasional words.
Keywords: term; verbal domain; style creator; a term of military significance; repentance; sin; main word of contrast; a term’s direct and metaphorical meaning; anthropologist; theologian